Estudio de factibilidad para la implementación de una minivan de hamburguesas express y su comercialización en la ciudad de Loja - Ojeda Prieto, Israel Alexander (2015)
The rate of business creation in an economy, it is essential to measure progress in a city factor, being essential to launch new businesses to benefit the economy in crucial areas such as increased competitiveness. The primary goal in creating a company is constantly innovating in order to provide higher quality and diversity of products and services offered to enlist the forefront of customers' requirement, since there is currently poor competitiveness because no innovation and variety in products and services in market segments related to business, especially sales of burgers offered. According to the monotony and lack of originality of existing businesses in the field of research potential and actual customers seek new markets where they can meet their expectations since they are fundamental needs for every human being. To study the deductive, inductive, synthetic and analytical methods and techniques such as direct observation, survey and interview they were used. The study begins with a situational analysis of the environment in which the company proposed would unfold; the rate of population growth in the city of Loja, and its trend of expansion and growth. Immediately market research in which the demand for this service is determined is presented. As to offer this service in the city of Loja is known that there are 28 companies that provide this service. As for the organizational structure that plays a key role in project implementation, it is important to emphasize the involvement of people needed for administration and operational area in total of 6 people, for the marketing of burgers. Therefore the organizational structure and functions Manual for all people who work in that company is determined. The total fixed assets is $ 38,813.50 US dollars, Deferred Assets $ $ 2,715.00 and $ 6,876.01 of current assets, totaling $ Investment $ 48,404.51; which 38.02% will be funded by the contributing partners and the rest it will be financed with a loan from the National Development Bank. He applied the main criteria for making the financial evaluation of the project was determined that the net present value is positive with a value of $ 64,702.81; the internal rate of return of 35.26% according to that comparison is greater than the rate of opportunity cost of capital of 12%; the cost-benefit ratio indicates that for every dollar invested will get $ 0.18 cents return, the investment will be recovered in three years, 08 months and 01 days. Consistent with these results and associated with the remainder of the study demonstrated that the implementation of the proposed project is feasible. Finally, conclusions were made determining the feasibility of project implementation because the planned investment may finance; the conditions exist to implement the company and especially the financial evaluation indicators determine the feasibility of implementation. Likewise, the implementation of the project which will be a small company with a high performance is recommended